IMPLEMENTATION OF MAQĀṢID AL-SYARĪ’AH AS MODEL GOVERNMENT’S POLICY AT MALANG CITY ON PERIOD 2011-2016 - Imana, Anis Ni’am (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2018)
This article focuses on the disclosure of social welfare development policies using maq± ṣid al-shar³’ah , namely religion ( al-d³n ), reason ( al-‘aql ), soul ( al-nafs ), descent ( al-nasl ), and property ( al-m±l ) as a model of welfare development in Malang City. The need for unmet basic rights can cause economic problems. The Human Development Index (HDI) in measuring human welfare is inadequate because it does not take into account aspects of spiritual well-being. This paper discusses the application of maqashid al-shariah as a model of government policy in the city of Malang. This study uses a qualitative approach with data collected from interviews, observation, and documentation. The results of this study indicate that the development of public welfare and strategies implemented by the Government of Malang are (a) the preservation of religion ( ḥifẓ al-d³n ) through religious and tolerant programs; (b) preservation of reason ( ḥifẓ al-‘aql ) by creating educated people; (c) maintaining the soul ( ḥifẓ al-nafs ) through the development of a clean, healthy community, as well as providing excellent public services; (d) descent conservation ( ḥifẓ al-nasl ) through child and pregnant women’s health counseling services; and (e) the preservation of property ( ḥifẓ al-m±l ) through the improvement of the regional economic sector, the creation of tourism cities, and the construction of local infrastructure